Are Polyunsaturated Fatty Acids Implicated in Histaminergic Dysregulation in Bipolar Disorder?: AN HYPOTHESIS - Riveros, María E.; Retamal, Mauricio A. (Frontiers in Physiology, 2018)
Bipolar disorder (BD) is an extremely disabling psychiatric disease, characterized by alternate states of mania (or hypomania) and depression with euthymic states in between. Currently, patients receive pharmacological treatment with mood stabilizers, antipsychotics, and antidepressants. Unfortunately, not all patients respond well to this type of treatment. Bipolar patients are also more prone to heart and metabolic diseases as well as a higher risk of suicide compared to the healthy population. For a correct brain function is indispensable a right protein and lipids (e.g., fatty acids) balance. In particular, the amount of fatty acids in the brain corresponds to a 50–70% of the dry weight. It has been reported that in specific brain regions of BD patients there is a reduction in the content of unsaturated n-3 fatty acids. Accordingly, a diet rich in n-3 fatty acids has beneficial effects in BD patients, while their absence or high levels of saturated fatty acids in the diet are correlated to the risk of developing the disease. On the other hand, the histamine system is likely to be involved in the pathophysiology of several psychiatric diseases such as BD. Histamine is a neuromodulator involved in arousal, motivation, and energy balance; drugs acting on the histamine receptor H3 have shown potential as antidepressants and antipsychotics. The histaminergic system as other neurotransmission systems can be altered by fatty acid membrane composition. The purpose of this review is to explore how polyunsaturated fatty acids content alterations are related to the histaminergic system modulation and their impact in BD pathophysiology.